Alternatives to antibiotics for sustainable livestock production in the context of the One Health approach: tackling a common foe - Ibeagha-Awemu, Eveline M.; Omonijo, Faith A.; Piché, Laurie C.; Vincent, Antony T. (Frontiers in Veterinary Science, 2025)
The discovery of the growth promoting effects of antibiotics in the 1940s contributed to the economic efficacy of the livestock industry. In response to increased animal protein demand from the 1950s, antimicrobial use at sub-therapeutic levels for growth promotion and disease prevention (antimicrobial growth promoter, AGP) improved feed-to-weight ratio, meat quality and overall health of livestock. These benefits encouraged the heavy use of AGPs such that about 70% of global use of antimicrobials was for food animals. Despite the numerous benefits of AGPs, the emergence of antimicrobial resistance (AMR) associated with their use and impact on human and livestock health, establishes AMR as a global health plague, affecting man, animal and the environment. Although many countries have banned the use of AGPs in livestock production, efforts to identify effective alternatives have yielded inconsistent findings and only few effective alternative products are currently available. This highlights the need to intensify efforts toward identifying more effective AGP alternatives. While current strategies focus on evaluating the efficacy of single products/class of products that can enhance productivity and health, future strategies should focus on combining multiple approaches. It is also important to acknowledge that no single alternative can fully replicate the same mechanism of action attributed to antimicrobials. This comprehensive review presents recent research findings on AGP use trend before and after bans in many countries, the benefit/mode of action of reported AGP alternatives, the economic impact of AGP alternatives in the context of the One Health approach, the factors militating the search for effective AGP alternatives, research gaps and future action plans for AGP-free animal farm management.